Venda Nova II powerhouse complex: geomechanical characterization, numerical modeling and back analysis of geomechanical parameters - Miranda, Tiago F. S. (2011)
In this paper, aspects concerning the geomechanical characterization related to the case study of the underground complex of Venda Nova II built in the North of Portugal are presented. Focus is drawn to the extensive in situ characterization performed by LNEC. A statistical study was carried out in order to establish reliable confidence intervals for the parameters. A 3D model for the powerhouse complex was developed and used together with the monitored displacements and an advanced optimization algorithm to back analyze geomechanical parameters. The back analysis study validated the parameters obtained by the in situ survey and proved to be a reliable complement in this characterization.